Adequate Antenatal Care Visits among Tribal Women in Bangladesh - Rezaul Karim, A.N.M. (Journal of Techno-Social, 2020)
Maternal mortality is a global concern, and peaks in developing countries. Adequate antenatal care services (ANCs) are indispensable for both maternal and fetal survival. A global trend leads us to the notion that aboriginal women are somewhat less privileged than non-tribal mothers around the world. Hence, this study determines the association of socio-economic status and adequate use of ANC facilities by Bangladesh’s tribal women. This study is a quantitative study using a convenient sampling technique. Semi-structured questionnaires were used to obtain data on married women (n=556) between the ages of 15â€“49 who had children aged 1 year or under. The data were analyzed using the SPSS program (version 20). Associations were determined using Chi-square test and regression analysis of maternal health care services and the adequacy of ANC use. Significance was determined at p-value <0.10. Results show that only 29.9% of pregnant tribal women sought ANC services, of which 13.5% visits hospital for ANC services four times or more during pregnancy. Significant association between age at first marriage, religion, family planning with adequate use of ANC services was observed. This study concludes that womenâ€™s education, occupation, state of the economy, residence location, and distance from health care facilities all positively influences the adequate use of ANC services. Thus, upgrading socioeconomic status, decentralization of health facilities and womenâ€™s education is recommended for adequate utilization of ANC services.